Advanced management accounting - Kaplan, Robert S. (Englewood Cliffs, N.J. : Prentice-Hall, 1982)
"The purpose of this text is to teach students how to apply analytic reasoning and use formal models when designing and evaluating management accounting systems. Management accounting systems collect, classify, summarize, analyze, and report information that will assist managers in their decision making and control activities. Historically, management accounting has evolved from the need to assign costs to products for external financial reports. Introductory cost accounting textbooks initially emphasized these cost allocation issues but during the twenty years, these texts have expanded their coverage to include the use of cost data for decisions and control within the firm. Thus, these texts now treat topics such as cost-volume-profit analysis, budgeting and planning, capital budgeting, and variance analysis of standard cost systems. This book closes the gap between management accounting research and practice. The book assumes that students have previously taken an introductory cost accounting course that covered topics such as job order costing, full and direct costing, standard costing with flexible budgeting, variance analysis and budgeting. These topics are generally well treated in introductory courses and require little expansion in an advanced textbook. The focus in this book wi be on the firm's planning and control decisions that require a more sophisticated approach than the rule-of-thumb procedures advocated for traditional cost accounting problems."
Includes bibliographies and indexes.
English text.
Keywords: Managerial accounting